Playing for progress: policy advocacy in sport for development - Moustakas, Louis; Carney, Sarah; Fischer, Sally-Ann J.; Richardson, Alana; Petry, Karen; Svoboda, Arnost; Hofmann, Ansley; Sanders, Ben (Frontiers in Sports and Active Living, 2025)
Sport for development (SFD) has emerged as a significant field of activity and has increasingly been critiqued for focusing on micro-level initiatives as a remedy to larger scale social or structural issues. This has led numerous scholars to propose more political meso or macro level approaches to deliver improved, sustainable outcomes. One such solution involves direct engagement in policy advocacy to support, and influence, policies that can directly benefit participants in SFD programmes. Against this background, our paper maps policy advocacy in the SFD field. Using results generated from a survey initiated in the context of a pan-European project, we map out the policy advocacy areas, activities and relationships within the sector. Our results show that most organisations engage in some form of advocacy, but much of this appears limited to the kind of self-interested advocacy that is designed to secure funding for organisational activities. Based on this, we argue that SFD actors should also engage in more progressive advocacy and suggest how research, as well as educational programming, can support this shift.